Extraction of Vegetable Oil from Candlenut Seeds (Aleurites Moluccana L. Willd.) Using the Microwave Hydrodiffusion and Gravity (MHG) Method - Yeni Variyana; Amelia Sri Rezki; Dewi Ermaya; Mahfud Mahfud (Universitas Muslim Indonesia, 2023)
The microwave hydriffusion gravity (MHG) method is a relatively new extraction method in order to improve the quality of oil obtained from plant materials or spices. The extraction process is carried out without involving solvents so it is safe for consumption. However, the MHG method has never been applied to the extraction of candlenut (Aleurites moluccana L) seeds. The operating conditions and variables in the research on the extraction process of Aleurites moluccana L are microwave power (300; 450; 600 W), extraction time (15-75 minutes) with 15-minute intervals, material size (1;2;3 cm), mass of raw material 100 gr, and atmospheric pressure. Material treatment consisted of 3 types of material conditions including seed material which had been roasted for 10 minutes over low heat, seed material which had been in the oven for 45 minutes, and seed material which had been without pretreatment. The results of the oil extract were analyzed using GC-MS to identify the components of the constituent compounds. Then, evaluating the mathematical modeling of the extraction process is based on first and second order kinetics. Roasted material showed the highest yield with material size parameter in 1 cm, microwave power of 600 W, and extraction time at 30 minutes, produced 5.55% (%w/w). Furthermore, the pyrazine component (36.814%) is the largest compound from the extraction of Aleurites moluccana. The first-order kinetic model has a regression that is close to the experiment with (R2 = 0.9453). Modeling quality is also supported by a very small total sum of squares (SST) value of 6,44E10-4. Therefore, the MHG method is quite effective in producing Aleurites moluccana oil with better quantity and quality